Treatment of arteriovenous malformation with high-flow fistula and bilateral transverse-sigmoid sinuses stenosis resulting diffuse cortical vein engorgement and symptoms resembling carotid-cavernous fistula - Chen, Kuo-Wei; Su, I-Chang; Lee, Jing-Er; Liu, Hon-Man (Asian Journal of Neurosurgery, 2015)
Patients harboring arteriovenous malformations (AVMs) may present with focal neurological deficit, seizures, hemorrhage or be completely asymptomatic. This diversity in manifestation of AVM is related to the individual characteristics of AVMs such as size, location, configuration of feeding arteries, and drainage veins. Treating the AVMs with high-flow fistula and downstream sinuses occlusion is challenging. The authors reported their experience of treating this kind of AVM. The high venous pressure caused diffuse cortical venous regurgitation and engorgement of left superior ophthalmic vein and symptoms resembling carotid-venous fistula. To avoid possible reflux of embolization materials to cortical veins and facilitate surgical treatment, the bilateral transverse sinuses were re-canalized first. The venous pressure was measured through left transverse sinus, and it decreased significantly from 50 mmHg to 20 mmHg after bilateral sinus stenting. The AVM was then embolized and excised uneventfully.
Keywords: Arteriovenous malformation; sinus occlusion; venous hypertension